Enhancing Employee Innovation Through Digital Talent Development: The Mediation of Digital Competency, Leadership and Culture in the Telecom Industry - Fauziah, Nadira Aribah; Sukmawati, Anggraini; Sartono, Bagus (Dinasti Publisher, 2026)
In the digital economy, innovation is a strategic imperative for sustaining organizational competitiveness, with employees’ innovative work behavior serving as a crucial micro-level foundation. Accelerated technological change and skill disruption have intensified the need for systematic digital talent development. Despite increasing scholarly attention to digital talent management, empirical research remains limited in explaining how digital talent development interacts with digital leadership, digital competence, and digital culture to shape innovative work behavior. This study addresses this gap by examining the structural relationships among these digital enablers within the context of digital transformation in the telecommunications industry. This study adopts a quantitative approach using survey data collected from 189 certified digital talents across PT Telkom Indonesia. Structural Equation Modeling–Partial Least Squares was employed to test the hypothesized relationships and mediating mechanisms. The results demonstrate that digital talent development influences innovative work behavior through an integrated mediating mechanism involving digital leadership, digital competence, and digital culture. This study advances the digital transformation literature by clarifying the systemic role of organizational enablers in translating digital talent investments into employee-level innovation. It emphasizes the necessity of aligning talent development with leadership capability, competency, and cultural reinforcement to support sustainable innovation in digitally transforming organizations.